Studies Of Rheumatoid Disease : Proceedings Of The Third Conference On Research In The Rheumatic Diseases T. (Heritage., 1966)
This publication is derived from the proceedings of the Third Canadian Conference on Research in the Rheumatic Diseases, sponsored jointly by the Canadian Rheumatism Association (the professional organization) and The Canadian Arthritis and Rheumatism Society (the voluntary association).